Effects of concurrent endurance and strength training on running economy and VO2 kinetics - Millet, G. P.; Jaouen, B.; Borrani, F.; Candau, R. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: It has been suggested that endurance training influences the running economy (CR) and the oxygen uptake (VO2) kinetics in heavy exercise by accelerating the primary phase and attenuating the VO2 slow component. However, the effects of heavy weight training (HWT) in combination with endurance training remain unclear. The purpose of this study was to examine the influence of a concurrent HWT+endurance training on CR and the VO2 kinetics in endurance athletes. METHODS: Fifteen triathletes were assigned to endurance+strength (ES) or endurance-only (E) training for 14 wk. The training program was similar, except ES performed two HWT sessions a week. Before and after the training period, the subjects performed 1) an incremental field running test for determination of VO2max and the velocity associated (VVO2max), the second ventilatory threshold (VT2); 2) a 3000-m run at constant velocity, calculated to require 25% of the difference between VO2max and VT2, to determine CR and the characteristics of the VO2 kinetics; 3) maximal hopping tests to determine maximal mechanical power and lower-limb stiffness; 4) maximal concentric lower-limb strength measurements. RESULTS: After the training period, maximal strength were increased (P < 0.01) in ES but remained unchanged in E. Hopping power decreased in E (P < 0.05). After training, economy (P < 0.05) and hopping power (P < 0.001) were greater in ES than in E. VO2max, leg hopping stiffness and the VO2 kinetics were not significantly affected by training either in ES or E. CONCLUSION: Additional HWT led to improved maximal strength and running economy with no significant effects on the VO2 kinetics pattern in heavy exercise.